2017
DOI: 10.1080/14728222.2017.1322065
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of acid ceramidase as a therapeutic target for acute myeloid leukemia

Abstract: Introduction Acute myeloid leukemia (AML) is the most common adult leukemia. Only a fraction of AML patients will survive with existing chemotherapy regimens. Hence, there is an urgent and unmet need to identify novel targets and develop better therapeutics in AML. In the past decade, the field of sphingolipid metabolism has emerged into the forefront of cancer biology due to its importance in cancer cell proliferation and survival. In particular, acid ceramidase (AC) has emerged as a promising therapeutic tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 79 publications
(94 reference statements)
1
16
0
Order By: Relevance
“…In cases where the enzyme becomes inactivated, recombinant aCDase is a potential treatment of maladies such as FD and SMA-PME, and the structure could provide an avenue of improvement for enzyme replacement therapy 24 . Finally, overexpression of aCDase has been linked to several cancers and there are ongoing attempts to design inhibitors that sensitize cancer cells to therapeutic treatments 4 , 22 . In this regard, the detailed knowledge of the substrate-binding site and mechanisms of autocleavage and ceramide hydrolysis will pave the way for the development of therapeutic inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases where the enzyme becomes inactivated, recombinant aCDase is a potential treatment of maladies such as FD and SMA-PME, and the structure could provide an avenue of improvement for enzyme replacement therapy 24 . Finally, overexpression of aCDase has been linked to several cancers and there are ongoing attempts to design inhibitors that sensitize cancer cells to therapeutic treatments 4 , 22 . In this regard, the detailed knowledge of the substrate-binding site and mechanisms of autocleavage and ceramide hydrolysis will pave the way for the development of therapeutic inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, aCDase is a critical target for inhibitor development in diseases involving excess hydrolysis of ceramide and accumulation of sphingosine-1-phosphate, and for enzyme replacement therapy in diseases caused by dysfunctional aCDase. Indeed, aCDase was suggested as a drug target for treatment of AML and pediatric brain tumors 22 . Moreover, injection of lentivectors encoding wild-type human-aCDase rescued the phenotype observed in mice encoding a faulty enzyme 23 and there is ongoing pharmaceutical interest in developing recombinant aCDase for FD and SMA-PME 24 .…”
Section: Introductionmentioning
confidence: 99%
“…In cancer research, a vast majority of the studies have been devoted to acid ceramidase (ACDase). This enzyme was reported as overexpressed in a myriad of tumor types including prostate (Saad et al, 2007), head and neck squamous cell (Elojeimy et al, 2007), and acute myeloid leukemia (AML) (Tan, Pearson, Feith, & Loughran, 2017). In vitro and in vivo studies have shown that by overexpressing ACDase, tumors are more aggressive and resistant to chemotherapies (Beckham et al, 2012; Saad et al, 2007).…”
Section: Effects Of Chemo- and Radiation Therapieson Sphingolipidsmentioning
confidence: 99%
“…Since its products are involved in the regulation of cell proliferation, multiple studies have linked ASAH1 to multiple cancers such as melanoma, acute myeloid leukemia (AML), and colon and prostate cancers [ 80 , 81 , 82 , 83 , 84 ]. ASAH1 has been proposed as an emerging drug target in AML [ 85 ]. Interestingly, over-expression of ASAH1 in prostate cancer promotes resistance to chemotherapy.…”
Section: Acid Ceramidase ( Asah1 ) As a Druggabmentioning
confidence: 99%